Sonographic demonstration of fetal esophagus using three‐dimensional ultrasound imaging. (4th November 2019) - Dall'Asta, A.; Grisolia, G.; Nanni, M.; Volpe, N.; Schera, G. B. L.; Frusca, T.; Ghi, T.
ABSTRACT: Objective: To evaluate the feasibility of antenatal direct visualization of normal and abnormal fetal esophagus using three‐dimensional ultrasound (3D‐US) with Crystal Vue rendering technology. Methods: Between February and April 2018, 3D‐US volumes were collected from a non‐consecutive series of singleton pregnancies, referred for clinically indicated detailed prenatal ultrasound at 19–28 weeks' gestation to one of two fetal medicine units in Italy. 3D volumes were acquired from a midsagittal section of the fetal thorax and upper abdomen with the fetus lying in supine position. Postprocessing with multiplanar mode was applied to orientate the volume and identify the esophagus. The region of interest was angled by approximately 30° to the spine and its thickness was adjusted in order to optimize visualization of the intrathoracic and intra‐abdominal course of the esophagus. Crystal Vue software was used for image rendering of the fetal trunk in the coronal plane. Postnatal follow‐up was available in all cases. Results: During the study period, 91 pregnancies met the inclusion criteria and were recruited. The study cohort included two pregnancies with suspicion of esophageal atresia due to suboptimal visualization of the stomach. Of the 89 cases with normal stomach on two‐dimensional (2D) imaging, 3D‐US with Crystal Vue rendering technology allowed direct evaluation of the whole course of the esophagus in 74 (83.1%). In the two cases with small or absent stomach bubble on 2D imaging, esophageal atresia was demonstrated antenatally on 3D Crystal Vue imaging and was confirmed postnatally. The mean time required for offline postprocessing and visualization of the esophageal anatomy was 4 min. Conclusions: Using 3D‐US with Crystal Vue rendering, it is possible to visualize antenatally the normal fetal esophagus and demonstrate presence of esophageal atresia. This should facilitate prenatal counseling and management of cases with suspected esophageal atresia. Copyright © 2019 ISUOG. Published by John Wiley & Sons Ltd.